Distribution Heterogeneity of Muscle Spindles Across Skeletal Muscles of Lower Extremities in C57BL/6 Mice - Lian, Wenxi; Hao, Fei; Hao, Peng; Zhao, Wen; Gao, Yudan; Rao, Jia-Sheng; Duan, Hongmei; Yang, Zhaoyang; Li, Xiaoguang (Frontiers in Neuroanatomy, 2022)
Muscle spindles, an important proprioceptor scattered in the skeletal muscle, participate in maintaining muscle tension and the fine regulation of random movement. Although muscle spindles exist in all skeletal muscles, explanations about the distribution and morphology of muscle spindles remain lacking for the indetermination of spindle location across muscles. In this study, traditional time-consuming histochemical technology was utilized to determine the muscle spindle anatomical and morphological characteristics in the lower extremity skeletal muscle in C57BL/6 mice. The relative distance from spindles to nerve-entry points varied from muscles in the ventral-dorsal direction, in which spindles in the lateral of gastrocnemius were not considered to be close to its nerve-entry point. In the longitudinal pattern, the domain with the highest abundance of spindles corresponded to the nerve-entry point, excluding the tibialis anterior. Spindles are mainly concentrated at the middle and rostral domain in all muscles. The results suggest a heterogeneity of the distribution of spindles in different muscles, but the distribution trend generally follows the location pattern of the nerve-entry point. Histochemical staining revealed that the spindle did not have a symmetrical structure along the equator, and this result does not agree with previous findings. Exploring the distribution and structural characteristics of muscle spindles in skeletal muscle can provide some anatomical basis for the study of muscle spindles at the molecular level and treatment of exercise-related diseases and provide a comprehensive understanding of muscle spindle morphology.